Anti-immunoglobulin E therapy: is it a valid option for the management of chronic rhinosinusitis with nasal polyposis? - Ashraf A. Wahba (The Egyptian Journal of Otolaryngology, 2019)
Abstract Objectives To evaluate the efficacy of omalizumab (OMA) therapy for patients with chronic rhinosinusitis with nasal polyposis as a sole therapeutic line versus traditional therapy. Patients and methods Eighty-six patients were randomly divided into two equal groups: study patients received OMA [0.016 mg/kg/immunoglobulin E (IgE) (IU/ml)] therapy only and control patients received conventional therapy. All patients completed a questionnaire to determine the total subjective score (TSS), who underwent rigid nasal endoscopy for endoscopic scoring according to the Lund-Kennedy scoring system, had paranasal sinuses computed tomographic (CT) imaging for scoring according to the Lund-Mackay scale, and estimation of pretreatment serum IgE levels. Study outcomes included the therapeutic effect determined as more than 50% decrease of TSS with improvement on endoscopic findings, recurrence rate, and frequency of decision; shift to surgery or repeat the trial of OMA therapy. Results Serum IgE level positively correlated with TSS and endoscopic and CT scores. Seventeen patients had successful response without recurrence with significantly lower TSS in the study versus control patients. Twenty-seven patients had recurrence after primary successful outcome with significantly lower TSS in study than control patients and significantly longer duration till recurrence with OMA than conventional therapy. Forty-two patients showed no response to the first session of therapy. Nineteen study patients with recurrent manifestations received a second session of OMA therapy; 11 had successful response, five patients had rerecurrence, and three patients failed to respond. Surgery-sparing effect is significantly higher with OMA than conventional therapy (46.5 vs. 18.6%). Endoscopic and CT scores of total patients, at the end of follow-up, were nonsignificantly lower in control while they were significantly lower in the study group. Conclusion OMA significantly superiorly improved the outcome of conservative treatment of chronic rhinosinusitis with nasal polyposis than conventional with higher surgery-sparing rate. The second session of OMA minimized the recurrence rate of manifestations.